A Peculiar Incident: Tracing Balinese Architectural Knowledge through Rewatching “Petualangan Sherina” Upon Mount Agung’s Eruption - Dewa Ayu Eka Savitri Sastrawan (Architectural Research Journal, 2025)
The 2017 eruption of Mount Agung caused significant alarm among both tourism stakeholders and the central government simultaneously. This was not only due to the sudden eruption after fifty years of dormancy, but also because of a deeper issue reflecting the inherently selfish tendencies of humans. A mountain - literally part of the natural world - was instead perceived as an obstacle to tourism revenue, since visitors could no longer travel to Bali. It was an ironic situation, as if tourism property were more important than the natural event itself, despite the fact that, according to local belief, the eruption was timely and necessary, serving as a natural balance within which all living beings exist. During this period, the author experienced the unusual circumstance of rewatching the film Petualangan Sherina (Sherina’s Adventure) on a flight to Bali, after being stranded outside the island for several days due to the eruption and the closure of Ngurah Rai Airport. This peculiar incident raised numerous questions and prompted the author to explore Balinese architectural knowledge through various writings, as well as art and architectural exhibitions held in 2017.